Analisis Semiotika Roland Barthes pada Bukhur dalam Tradisi Islam - Nurul Shabah; El Bilad, Cecep Zakarias; Khair, Muhammad Saiful (Moderasi: Jurnal Studi Ilmu Pengetahuan Sosial, 2023)
This article discusses bukhur is a small piece of aromatic wood or a mixture of traditional natural ingredients, with the main ingredient being wood (oudh) soaked in fragrant oil and blended with other natural materials. The purpose of this research is to understand bukhur in the Islamic tradition by identifying its denotation, connotation, and mythology found within the symbol of bukhur. This research method employs a qualitative descriptive research approach. The data analysis in this study utilizes Roland Barthes' semiotic analysis, which employs the signifier and signified system to explore denotation, connotation, and myths associated with bukhur. And this research result explains that by using semiotic analysis, it can be understood how signs and symbols in the incense burner play an important role in shaping religious identity.